2008
DOI: 10.1007/s00018-008-8490-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential insult-dependent recruitment of the intrinsic mitochondrial pathway during neuronal programmed cell death

Abstract: Programmed cell death contributes to neurological diseases and may involve mitochondrial dysfunction with redistribution of apoptogenic proteins. We examined neuronal death to elucidate whether the intrinsic mitochondrial pathway and the crosstalk between caspase-dependent/-independent injury was differentially recruited by stressors implicated in neurodegeneration. After exposure of cultured cerebellar granule cells to various insults, the progression of injury was correlated with mitochondrial involvement, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 54 publications
3
33
0
Order By: Relevance
“…5B). Due to cytochrome c and caspase-9 elevation, the caspase-dependent pathway of intrinsic apoptosis may play important roles in cell apoptosis (41,42). It was reported that caspases are a family of cysteine proteases that play a central role during the executional phase of apoptosis (43).…”
Section: Discussionmentioning
confidence: 99%
“…5B). Due to cytochrome c and caspase-9 elevation, the caspase-dependent pathway of intrinsic apoptosis may play important roles in cell apoptosis (41,42). It was reported that caspases are a family of cysteine proteases that play a central role during the executional phase of apoptosis (43).…”
Section: Discussionmentioning
confidence: 99%
“…In neuronal cells, it has been observed that AIF and endonuclease G are released from mitochondria much later than cytochrome c [Beart et al, 2007;Diwakarla et al, 2009] and the release may be mediated by caspases or calpains [Polster et al, 2005] as it was sensitive to inhibitors of these proteases whereas the release of cytochrome c was insensitive. These data suggest that the loss of cytochrome c from mitochondria is not mediated by caspases; however, activated caspases may have a feed-back effect on mitochondria promoting the release of additional factors into the cytosol ensuring completion of apoptotic cell death.…”
Section: Consequences Of Permeabilization Of Mitochondrial Membranesmentioning
confidence: 98%
“…Our ongoing work employing primary cultured neurons (cerebellar granule cells, [46]) has explored the pharmacological inhibition of the respiratory chain, to provide an approach considered to mimic the loss of electron flux, under pathological conditions. This entails a re-examination of the actions of selective inhibitors of complexes I-IV, thus placing this work in a contemporary context ( [47] and Shin YS and Beart PM, unpublished observations).…”
Section: Mitochondrial Respiratory Complexes Oxidative Damage and Pcdmentioning
confidence: 99%
“…A number of studies have reported the involvement of AIF as the main executioner, in the absence of caspase activity, following cerebral hypoxia-ischemia in primary neuronal cultures [46,[122][123][124]. AIF is a mitochondrial IMS protein that is redistributed to the cytosol where it translocates to the nucleus to bring about DNA fragmentation within the nucleus.…”
Section: Acute Oxidative Stress: Autophagy and Programmed Necrosismentioning
confidence: 99%